Maximum oxygen uptake vs level of performance in judo - Blasco-Lafarga, C.; Pablos Abella, C.; Garrido Chamorro, R. P. (Archivos de medicina del deporte, 2008)
Introduction: There is some controversy about the utility of increasing the VO2max to improve the performance in judo, though many studies point to the benefi ts. We have studied the relationship between VO2max and performance in Judo, analysing whether there are signifi cant differences according to the sporting level, and comparing what happens with this same analysis when assessing performance through a specifi c judo test. Material and methods: We have made a descriptive study with 26 male Spanish judoists (national and international level; 21.12±3.32 years; 74.53±9.79 kg, 11.36±2.10% of fat, 58.22±7.16% of muscle mass) divided into three groups have made an anthropometry, a treadmill VO2max test (Wasserman protocol), and a specifi c judo test, looking for statistically signifi cant differences in each case (one way ANOVA) related to that level. VO2max has been analysed in relative terms, depending on the fat-free mass (FF), and muscle mass (MM). Results: Comparing to what happened on the results of the Judo Test (Figure 1, Table 2: p< 0.001 between Very Good and Average judoists; also between Good and Average), we have not found signifi cant differences in any of the three expressions of VO2max analysed (Table 1). Despite this, the results of the Treadmill Test have been adequate (VO2max: 60.37±9.44 ml/kg/min; FFVO2max 67.99±9.89 ml/FFkg/min; MMVO2max: 103.32±14.35 ml/MMkg/min; Aerobic Maximum Speed: 17.33±1.58 km/h; FCM: 192.85±7.69 p/m; one minute recovery lactate: 9.63±2.47 mMol). Conclusions: There are no signifi cant differences in VO2max according to the level of performance; VO2max and FFVO2max show the same trend, while MMVO 2max shows different; VO2max allows comparing individuals in the same weight category, while MMVO2 seems to refl ect better the muscle effi ciency of each judoist; We need further studies to deepen in the relationship between MMVO2max and performance in Judo.